Hydrocephalus secondary to obstruction of the lateral apertures in two dogs. Issue 11 (November 2016) - Kent, M; Glass, EN; Haley, AC; Shaikh, LS; Sequel, M; Blas‐Machado, U; Bishop, TM; Holmes, SP; Platt, SR
Abstract : Background: Traditionally, hydrocephalus is divided into communicating or non‐communicating (obstructive) based on the identification of a blockage of cerebrospinal fluid (CSF) flow through the ventricular system. Hydrocephalus ex vacuo refers to ventricular enlargement as a consequence of neuroparenchymal loss. Hydrocephalus related to obstruction of the lateral apertures of the fourth ventricles has rarely been described. Case report: The clinicopathologic findings in two dogs with hydrocephalus secondary to obstruction of the lateral apertures of the fourth ventricle are reported. Signs were associated with a caudal cervical spinal cord lesion in one dog and a caudal brain stem lesion in the other dog. Magnetic resonance imaging (MRI) disclosed dilation of the ventricular system, including the lateral recesses of the fourth ventricle. In one dog, postmortem ventriculography confirmed obstruction of the lateral apertures. Microscopic changes were identified in the choroid plexus in both dogs, yet a definitive cause of the obstructions was not identified. The MRI findings in both dogs are similar to membranous occlusion of the lateral and median apertures in human patients. Conclusion: MRI detection of dilation of the entire ventricular system in the absence of an identifiable cause should prompt consideration of an obstruction of the lateral apertures. In future cases, therapeutic interventions aimed at re‐establishing CSF flow or ventriculoperitoneal catheterisation should be considered.